Investigation the Effectiveness of Chronic Agomelatine on Foetal Number in before and Different Periods of Pregnancy in Rats - Tan, Fatih; Sahinturk, Serdar; Zorlu, Gokhan; Serhatlioglu, Ihsan; Ercan, Zubeyde; Bulmus, Ozgur; Kacar, Emine (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY